A novel approach to the synthesis of layered structures - Maifadi, Sebabatso (My University, 2016)
The synthesis of pure layered clay minerals has to be evaluated at low temperatures, pressures and short reaction times to scale up to commercial processes. However, it has been discovered that under such reaction conditions, reactions experience considerable difficulties. Such difficulties include low yields of products that occur with associated other minerals, and long reaction times. Thus, the synthesis of synthetic clay minerals is commonly approached by the hydrothermal technique, which involves the crystallization of substances at high vapour pressures and temperatures. However, the employment of the hydrothermal technique is time- and water consuming, thus, the need for an energy-saving and reaction accelerating process method. In the work presented here particular interest is paid to the synthetic layered clay mineral pyrophyllite, which is used as a pressure transmitting medium in the making of synthetic diamond. As opposed to the hydrothermal technique, this work adopts the synthetic method resin gel for the synthesis of these layered materials. Preliminary results by Loren Purcell have shown that the resin-gel synthesis method has been able to make apparently layered materials that appear to have a thermal gravimetric profile that indicates a gradual mass loss of both surface and structural water. The work presented here reproduces these results and further explores other Si\Al ratio’s, silica and alumina precursors for the synthesis of pyrophyllite-like materials and the different heating methods of the gels. Transmission electron microscopy (TEM) shows that irrespective of the synthesis conditions sheet-like or platy crystals are formed. Scanning electron microscopy (SEM) confirms on the TEM observations and shows that the surface texture of the crystals has a compact appearance. Thermal gravimetric analysis (TGA) of the materials confirms on previous observations from preliminary results, materials indicate both adsorbed surface and interlayer water. Powder Xray diffraction (PXRD) is inconclusive of the determination of phase pure pyrophyllite. Furthermore, Brunauer-Emmett-Teller (BET) reveals that the materials are mesoporous solids and the materials were also characterised by DSC, Raman and HRTEM.
School of Chemistry, Faculty of Science, University of Witwatersrand, Johannesburg, South Africa Johannesburg, 2016
Keywords: Layer structure (Solid); Clay minerals